Identificación de paisajes y atractivos como aporte para el desarrollo turístico del Área Protegida Comunitaria “Marcos Pérez de Castilla”, cantón Oña, provincia de Azuay. - Ortega Girón, Astrid Verónica (2024)
The landscape is a very valuable resource for tourism, as it is that part of the territory that the human being perceives, individually or as a whole; based on their perception it will be their experience and their valuation supports the development of tourism. The research was carried out in the Community Protected Area “Marcos Pérez de Castilla”, canton Oña province of Azuay. The research set a general objective: To contribute to the tourist development of the Community Protected Area “Marcos Pérez de Castilla” through the identification of its landscapes and tourist attractions, supported by two specific objectives: Identify the landscapes and tourist attractions of the Community Protected Area “Marcos Pérez de Castilla” and design a catalogue of landscape and touristic attractions in the Community Prohibited Área “Marcos Pérez de Castilla”. Starting with the delimitation of landscape units by: geomorphology and plant coverage, to subsequently identify the landscapes, describe them according to their characteristics and components; formal structure and soil coverage. The tourist attractions were identified using the MINTUR maps, the visual landscaping resources according to three indicators; visual references, representative views and unique enclaves, the historical and current dynamics of each landscape; interviewing people of the third age, the landscaps were evaluated according to the quality of the land, social value and visibility, to culminate with the design of the catalogue photographs were taken. Thirty-five landscape units, five landscapes, seven tourist attractions and six visual landmarks were identified, the representative change is the migration of inhabitants, the most valued landscave is “Lagunas” and as a product of the research a catalogue of landscaps was obtained. It is concluded that the area has a considerable number of landscapes where tourism can be carried out due to the presence of tourist attractions, the predominant geoforms are high hills and medium hills, covered by shrubby moorland and herbaceous vegetation.